2008
DOI: 10.1523/jneurosci.4682-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Habituation Reveals Fundamental Chromatic Mechanisms in Striate Cortex of Macaque

Abstract: Prolonged viewing of a chromatically modulated stimulus usually leads to changes in its appearance, and that of similar stimuli. These aftereffects of habituation have been thought to reflect the activity of two populations of neurons in visual cortex that have particular importance in color vision, one sensitive to red-green modulation, the other to blue-yellow, but they have not been identified. We show here, in recordings from macaque primary visual cortex (V1), that prolonged exposure to chromatic modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 27 publications
6
49
1
Order By: Relevance
“…These effects were spatially specific but not tuned for stimulus orientation or spatiotemporal frequency and were attributed to retinal mechanisms. Finally, Tailby et al (2008) showed that adaptation with chromatically modulated stimuli can alter the color preference of V1 neurons, resulting in shifts in preference toward or away from the adapter, much like the effects we observed for orientation tuning. Each of these studies targets a distinct type of normalization signal with unique features and possibly a distinct origin.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These effects were spatially specific but not tuned for stimulus orientation or spatiotemporal frequency and were attributed to retinal mechanisms. Finally, Tailby et al (2008) showed that adaptation with chromatically modulated stimuli can alter the color preference of V1 neurons, resulting in shifts in preference toward or away from the adapter, much like the effects we observed for orientation tuning. Each of these studies targets a distinct type of normalization signal with unique features and possibly a distinct origin.…”
Section: Discussionsupporting
confidence: 71%
“…This rule results in an increase in threshold (i.e., a hyperpolarization) that is largest for strongly driven cells adapted at their preferred orientation ( prefϭ ϭ adapt ) and a decrease in threshold for cells adapted far from their preferred orientation ( pref Ϫ adapt ϭ90°). A conceptually similar model has been proposed to explain color and contrast adaptation effects in V1, but with an emphasis on the interaction between the excitatory and suppressive mechanisms within the CRF (Dhruv et al 2011;Tailby et al 2008).…”
Section: General Methods Before Surgery Monkeys (Macaca Fascicularis)mentioning
confidence: 99%
“…Such cells reside in V1 at or near the arrival of geniculate signals into the cortex (Livingstone and Hubel, 1984). Physiological experiments in monkeys indicate this stage as a potential substrate for the cardinal mechanisms (Tailby et al, 2008). This is an attractive idea because it preserves a defining role of the two major populations of color-coding LGN cells in generating the cardinal mechanisms yet is consistent with a cortical implementation suggested by the multiple lines of evidence discussed here.…”
supporting
confidence: 65%
“…Colors were defined by the Derrington-Krauskopf-Lennie (DKL) color space used in many psychophysical experiments in humans (Krauskopf et al, 1982(Krauskopf et al, , 1986Webster and Mollon, 1991;Gegenfurtner and Kiper, 1992;Hansen and Gegenfurtner, 2006) and physiological experiments in monkeys (Derrington et al, 1984;Lennie et al, 1990;Gegenfurtner et al, 1997;Tailby et al, 2008;Lafer-Sousa et al, 2012). The Judd-corrected Commission Internationale de l'É clairage xyY coordinates of all stimuli can be found at http://www.wellesley.edu/neuroscience/conway/stoughtonetal2012.…”
Section: Methodsmentioning
confidence: 99%
“…Contrast adaptation brings about a slow reduction in the responsivity of some retinal and LGN cells, and most neurons in visual cortex, that persists for several seconds after the removal of the adapting stimulus (Movshon and Lennie, 1979;Ohzawa et al, 1985;Sclar et al, 1985;Smirnakis et al, 1997;Brown and Masland, 2001; Chander and Chichilnisky, 2001; Baccus and Meister, 2002;Solomon et al, 2004;Duong and Freeman, 2007;Tailby et al, 2008). We distinguish the impact of this slow contrast adap-tation from that of contrast gain controls, which provide a rapid regulation of responsivity.…”
Section: Introductionmentioning
confidence: 96%